A review of customer citizenship behaviors in the service context. Issue 3 (17th February 2021) - Gong, Taeshik; Yi, Youjae
ABSTRACT: During the last two decades, studies on customer citizenship behavior in the service context have gained the attention of researchers. However, there is no comprehensive review exploring the various dimensions, antecedents, and consequences of customer citizenship behavior. The purpose of this paper is, therefore, to critically review the studies of customer citizenship behavior to provide deeper insights, which help us to identify the research gaps in this area and to prepare a future research agenda, and thereby contributing toward the development of this research field. The authors find that several areas were under-explored in prior research. There is a potential for identifying additional dimensions of customer citizenship behavior as well as the antecedents and consequences of customer citizenship behavior. The authors also assess methodological issues with regard to this research field and set a future research agenda.